Evaluation of Mindray BC‐5000 hematology analyzer: a new miniature 5‐part WBC differential instrument. (5th May 2015) - Xiang, D.; Yue, J.; Lan, Y.; Sha, C.; Ren, S.; Li, Y.; Li, M.; Wang, C.
Summary: Introduction: The Mindray BC‐5000 automated hematology analyzer is a miniature, automated hematology analyzer, and 5‐part leukocyte differential counter for in vitro diagnostic use in clinical laboratories. Methods: Precision, linearity, carryover, and method comparison were carried out. The analyzer was evaluated and compared with the Sysmex XE‐2100 hematology analyzer and manual microscopic in the hematology laboratory of a tertiary hospital in Chinese. Results: There were minimal carryover (<0.25%), and excellent linearity for white blood cell, and platelet counts ( r  > 0.99). Within‐run precision was good at all levels for the routine cell blood count parameters (CV < 3.5%). Between‐run precision was acceptable at all levels for the analysis parameters (CV < 5%) except for eosinophil and basophil (CV% >10%). BC‐5000 displayed very good correlation ( r  > 0.94) with the XE‐2100 for cell blood count and cell differential parameters except for basophil ( r  = 0.72). The comparison of 258 leukocyte differential count results analyzed in parallel with manual microscopy, BC‐5000 analyzer showed perfect specificity (93%) and negative predictive value (90%) on abnormal blood samples. Conclusion: It is concluded that the overall performance of the BC‐5000 is acceptable. The miniature analyzer is suitable for use in small‐ to medium‐size laboratories.